Childhood meningitis in the conjugate vaccine era: a prospective cohort study. Issue 3 (25th September 2014) - Sadarangani, Manish; Willis, Louise; Kadambari, Seilesh; Gormley, Stuart; Young, Zoe; Beckley, Rebecca; Gantlett, Katherine; Orf, Katharine; Blakey, Sarah; Martin, Natalie G; Kelly, Dominic F; Heath, Paul T; et al.
Abstract : Bacterial conjugate vaccines have dramatically changed the epidemiology of childhood meningitis; viral causes are increasingly predominant, but the current UK epidemiology is unknown. This prospective study recruited children under 16 years of age admitted to 3 UK hospitals with suspected meningitis. 70/388 children had meningitis—13 bacterial, 26 viral and 29 with no pathogen identified. Group B Streptococcus was the most common bacterial pathogen. Infants under 3 months of age with bacterial meningitis were more likely to have a reduced Glasgow Coma Score and respiratory distress than those with viral meningitis or other infections. There were no discriminatory clinical features in older children. Cerebrospinal fluid (CSF) white blood cell count and plasma C-reactive protein at all ages, and CSF protein in infants <3 months of age, distinguished between bacterial meningitis and viral meningitis or other infections. Improved diagnosis of non-bacterial meningitis is urgently needed to reduce antibiotic use and hospital stay.